Resveratrate protects human skin from damage due to repetitive ultraviolet irradiation. (5th January 2012) - Wu, Y.; Jia, L.‐L.; Zheng, Y.‐N.; Xu, X.‐G.; Luo, Y.‐J.; Wang, B.; Chen, J.Z.S.; Gao, X.‐H.; Chen, H.‐D.; Matsui, M.; Li, Y.‐H.
Abstract Background Ultraviolet (UV) exposure results in the production reactive oxygen species. Resveratrol has attracted considerable attentions owing to its natural abundance and multiple biological effects. Objective To investigate the protective effects of resveratrate against damage to human skin induced by repetitive solar simulator ultraviolet radiation (ssUVR). Materials and methods Fifteen healthy volunteers were enrolled, and six sites on the non‐exposed dorsal skin of each volunteer were marked for study. Sites 1–4 were exposed to ssUVR at a dosage of 1.5 minimal erythema dose for consecutive 4 days. Immediately after each exposure, one test material (resveratrate + antioxidant, antioxidant, resveratrate, vehicle) was applied to one of the four sites. Site 5 and site 6 were marked as positive control site (UVR only) and baseline control site (no treatment, no UVR). L*a*b values were assessed preprocedure and postprocedure. Skin biopsies were taken 24 h after the last irradiation. The specimens were stained to determine the number of sunburn cells and melanin content melanin. Results On resveratrate treated sites, erythema was barely seen with only slight decrease of L value and insignificant increase of *a value. Furthermore, resveratrate significantly inhibited sunburn cell formation, and decreased Fontana‐Masson staining in skin samples. Conclusions Resveratrate exerts protective effects against repetitive ssUVR‐induced sunburn and suntan.